Histomorphometric and radioimmunoassay studies of the rat endometrium following peanut oil treatment - Venant Tchokonte-Nana; Benjamin Longo-Mbenza (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: The pregnancy rate during in-vitro fertilization (IVF) following progesterone supplement still remains very low at around 20%.Objective: To investigate the effects of peanut oil itself on the endometrial receptivity, the pregnancy success rate and fertility during the peri-implantation time in hyper stimulated and normal rats. Materials and Methods: Thirty-six adult Sprague Dawley rats with at least four regular oestrus cycles were randomly divided into 4 groups: two groups were hyper stimulated by human chorionic gonadotropin (hCG) and treated with progesterone or with peanut oil; the two other groups were not hyper stimulated and treated with saline solution or peanut oil. On day 5.5 of pregnancy, the uterine horns were removed and blood was collected for histomorphometric and serum progesterone evaluation. 12 rats were allowed to continue the presumed pregnancy to term. Analysis of variance (ANOVA) and student t-test were used to compare the means of morphometric and radioimmunoassay data between groups. p-values less than 0.05 were considered statistically significant.Results: The mean values of morphometric parameters and serum progesterone varied significantly between the groups (ANOVA, p<0.0001). The lowest values of progesterone parameters were observed in the hyperstimulated groups that did not deliver pups; both hyperstimulated groups had deleterious luminal epithelium with varying degrees of mucosal projections. There were isolated decidualised zones observed in hyper stimulated peanut oil group, whereas peanut oil group had the highest number of implantation sites and deliveries.Conclusion: The results show that hype stimulation reduces the endometrial receptivity, while peanut oil increases endometrial receptivity, pregnancy rates and fertility by triggering decidualisation